Epigenetics of Triple-Negative Breast Cancer via Natural Compounds - Kaleem, Mohammed; Perwaiz, Maryam; Nur, Suza M.; Abdulrahman, Abdulrasheed O.; Ahmad, Wasim; Al-Abbasi, Fahad A.; Kumar, Vikas; Kamal, Mohammad Amjad; Anwar, Firoz (Current Medicinal Chemistry, 2022)
Triple-negative breast cancer (TNBC) is a highly resistant, lethal, and metastatic sub-division of breast carcinoma, characterized by the deficiency of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). In women, TNBC shows a higher aggressive behavior with poor patient prognosis and a higher recurrence rate during reproductive age. TNBC is defined by the presence of epithelial- to-mesenchymal-transition (EMT), which shows a significant role in cancer progression. At the epigenetic level, TNBC is characterized by epigenetic signatures, such as DNA methylation, histone remodeling, and a host of miRNA, MiR-193, LncRNA, HIF- 2α, eEF2K, LIN9/NEK2, IMP3, LISCH7/TGF-β1, GD3s, KLK12, mediated regulation. These modifications either are silenced or activate the necessary genes that are prevalent in TNBC. The review is based on epigenetic mediated mechanistic changes in TNBC. Furthermore, Thymoquinone (TQ), Regorafenib, Fangjihuangqi decoction, Saikosaponin A, and Huaier, etc., are potent antitumor natural compounds extensively reported in the literature. Further, the review emphasizes the role of these natural compounds in TNBC and their possible epigenetic targets, which can be utilized as a potential therapeutic strategy in the treatment of TNBC.
Keywords: DNA methylation